Akurasi dan Presisi Analisis Kadar Nikel (Ni) pada Sampel Nikel Laterit Menggunakan X-Ray Fluorescence Spectometry (XRF) - Yulianti Malik (Sains: Jurnal Kimia dan Pendidikan Kimia, 2023)
Testing laboratories are required to be able to produce reliable and accountable analysis results. In order to fulfill this, it is necessary to verify the method. Method verification has been carried out for accuracy and precision parameters for the analysis of nickel elements in laterite nickel ore using XRF based on the ASTM E1085-16 analysis method. The test results show that these two parameters meet the acceptance requirements, with an accuracy rate (TA) of 99.43%, and a low error rate of only around 0.57% and meet the acceptance test requirements with the Horwitz equation, namely 0.0100 ≤ 0.0156. Meanwhile, the precision (repeatability) test carried out also met the acceptance requirements which met the test requirements using the Horwitz equation with a ratio of %RSD < ½ CV Horwitz (0.4693 < 1.84005).